Dynamics of the Implementation of Experience-Based Religious Learning in Indonesian and Malaysian Senior High Schools - Kistoro, Hanif Cahyo Adi; Ru’iya, Sutipyo; Husna, Difaul; Burhan, Norhapizah Mohd (Jurnal Pendidikan Agama Islam, 2022)
Purpose – This study describes implementing the experiential learning-based spiritual learning model for high school students. Design/methods/approach – This research adopts a qualitative methodology with a narrative approach, focusing on thirteen Islamic religion teachers from both public and private high schools in Indonesia and Malaysia. Findings – This study divides the findings into three, namely teacher understanding, forms of application and constraints in experiential learning. Teachers' understanding of experiential learning based on this research is not evenly distributed. meaning that the teacher in theory does not know much but some have practiced it. the application of learning is carried out using online media. while the constraints faced came from internal and external factors. Research implications/limitations – This research recommends the use of experiential learning to enhance religious education. Teachers need to develop innovative learning strategies, while students should actively participate in the learning process and apply their experiences. The study also suggests that schools should incorporate experiential learning methods in their curriculum to enhance the effectiveness of religious education. These recommendations provide practical insights into developing religious education based on experiential learning. Originality/value – The study found similarities in the application of experiential learning in religious education between Indonesia and Malaysia, including the use of video media to increase students' interest in the material. However, both countries face similar obstacles, such as the need to increase teacher competence in innovative learning strategies, the presence of noise in new learning, and the need for standard syllabi.